Effect of the hydrophobic properties of a composite system on adsorption of dyes of different nature - Klymenko, N.Yu.; Krupska, T.V.; Turov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The adsorptive capacity of various silica with respect to cationic (methylene blue, MB) and anionic (congo red, CR) dyes has been studied. The adsorption of methylene blue from solutions simulating the stomach and intestine media has been provided. The adsorption isotherms obtained allow the adsorptive capacity of silicas in different simulating media to be determined. In the adsorption of methylene blue from an acidic solution (pH 1.5), the adsorption is reduced due to the electrostatic repulsion of the identically-charged dye components. Compaction of silica causes a reduction of the dye adsorption in the selected pH interval. It is demonstrated that the composite system based on a mixture of hydrophilic silica and hydrophobic silica has bet ter adsorption properties with respect to congo red as compared with compacted adsorbents. In the case of methylene blue, the adsorptive capacity of the А-300/АМ1-300 composite system is 2 and 3.7 times higher in the acidic pH interval as compared with compacted silicas (A-300 with Cd = 300 g/l, and A-300 with Cd = 175 g/l, accordingly). The adsorptive capacity of methylene blue is more than six times that of congo red. This feature may be caused by electrostatic interactions between the dye molecules and the surfaces of the silica particles.